Features of the Mechanisms of Conductivity of the Electrorheological Fluids With Double Doped TiO2 Particles Under External Temperature Effects - Korobko, Evguenia V.; Novikova, Zoya A. (Frontiers in Materials, 2019)
Electrophysical and rheological characteristics of ER fluids with TiO2 particles doped with alumi-num and phosphorus and having anatase structure are considered in an extended temperature range (5 - 100 ° C). The mechanisms of leakage currents in the ER fluid in electric fields up to 3.5 kV/mm are determined. Conduction mechanisms such as thermionic ionization, electron injection from an electrode, thermal excitation of charges, field emission of electrons from an electrode, thermionic emission of electrons from an electrode, and field emission of electrons from traps are identified. Based on the analysis of the current-voltage characteristics of the ER fluid, the positive role of the additional doping of the dispersed phase particles with phosphorus compared with the known results for ER fluid with TiO2/Al particles was established. The use of double doping of particles of the dispersed phase made it possible to obtain stable dependences of the shear stress of electrorheological fluids on the electric field strength in the range of the temperature effects under study.